Constructs of emotional intelligence and the performance of employees of registered eateries in an emerging economy - Vincent, Edewhor; Ernest, Eruteya Ejiro (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of Emotional Intelligence (EI) on employee performance in fast food outlets in Delta State, Nigeria. The objectives were to examine the influence of self-control, self-awareness, and social competency on employees’ performance. A quantitative research design was employed, utilizing a structured questionnaire distributed to 146 participants working in various fast-food establishments. The data collected were analyzed using descriptive statistics; Pearson correlation and regression analysis were used to identify relationships between emotional intelligence components and employee performance. The findings indicate that self-control and self-awareness significantly correlate with improved employee performance, with mean scores reflecting a strong capacity to manage emotions and build positive workplace relationships. Conversely, challenges were noted in avoiding impulsive actions and adapting to diverse personalities, emphasizing the implications of Emotional Intelligence (EI) in improving operational efficiency within the fast-food industry. Based on these findings, the study recommends implementing targeted emotional intelligence training programs to enhance employees’ self-control, self-awareness, and social competency, and establishing mentorship programs to guide employees in emotional regulation and team dynamics. Additionally, fostering a supportive work environment that encourages open communication and feedback is essential, among others. The study emphasizes the importance of EI as a key driver of employee performance and organizational success.